2019
DOI: 10.1016/j.jenvman.2019.04.121
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing habitat connectivity in the mitigation hierarchy. A case study on three terrestrial mammals in an urban environment

Abstract: Environmental policies and the objective of no net loss highlight the importance of preserving ecological networks to limit the fragmentation of natural habitats and biodiversity loss, especially due to urbanization. In the environmental impact assessment context, habitat connectivity and the spatio-temporal dynamics of biodiversity are crucial to obtaining reliable predictions that can support decision-making. We propose a methodological framework 1) to quantify the overall impact of a development project on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…Our results showed that the negative impacts of using only habitat-based metrics and ignoring species-specific connectivity may be significant, vary greatly among metrics, and, most alarmingly, are likely to go unnoticed unless changes in population dynamics are tested explicitly. These findings provide strong support for earlier calls that both structural (e.g., patch size and distance) and functional connectivity metrics (e.g., metapopulation connectivity and capacity [Moilanen et al 2005;Bojkovic et al 2015]) should be accounted for in early stages of impact assessment and offset planning to avoid unexpected declines in populations and species (Tarabon et al 2019).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results showed that the negative impacts of using only habitat-based metrics and ignoring species-specific connectivity may be significant, vary greatly among metrics, and, most alarmingly, are likely to go unnoticed unless changes in population dynamics are tested explicitly. These findings provide strong support for earlier calls that both structural (e.g., patch size and distance) and functional connectivity metrics (e.g., metapopulation connectivity and capacity [Moilanen et al 2005;Bojkovic et al 2015]) should be accounted for in early stages of impact assessment and offset planning to avoid unexpected declines in populations and species (Tarabon et al 2019).…”
Section: Discussionsupporting
confidence: 78%
“…2015]) should be accounted for in early stages of impact assessment and offset planning to avoid unexpected declines in populations and species (Tarabon et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our models could be improved by incorporating more qualitative developments, such as wildlife crossings. Wildlife crossings lead to landscape defragmentation and reconnect environments with each other, thereby enhancing the overall connectivity of ecological networks (Bergès et al, 2020;Mimet et al, 2016;Tarabon, Bergès, Dutoit, & Isselin-Nondedeu, 2019b).…”
Section: Tablementioning
confidence: 99%
“…In the light of recurrent failures in biodiversity offsetting implementation (see Bezombes et al, 2019;May et al, 2017;Weissgerber et al, 2019), there is growing evidence of the benefits of including landscape connectivity into the mitigation hierarchy (Dalang and Hersperger, 2012;Tarabon et al, 2019bTarabon et al, , 2020. A territorial-scale conservation strategy seems to further increase these benefits.…”
Section: Introductionmentioning
confidence: 99%